Penentuan Prioritas Kriteria dan Peringkat Pemasok Menggunakan AHP-TOPSIS di PT Sutindo Raya Mulia - Gunawan, Evelyn; Oktiarso, Teguh; Ekawati, Yurida (Teknik Industri Universitas Ma Chung, 2023)
Sutindo Raya Mulia is a stockist company that purchases, stores, and resells it to consumers. PT Sutindo Raya Mulia is headquartered in the city of Surabaya and has branch offices in Jakarta, Semarang, Balikpapan, and Samarinda. One of the products offered by SRM is a stainless steel plate. Plate products have 3 series (S200, S300, and S400) and have different suppliers consisting of both local and international. Some of the weaknesses of the purchasing process can be caused by the selection of suppliers that are not fixed when purchasing products from suppliers. This is because the company does not have priority criteria in selecting suppliers. Priority criteria are determined using the Analytical Hierarchy Process method. Supplier assessment is determined using the Technique for Order Preference by Similarity to Ideal Solution method. The results of the AHP method obtained the weight and order of these criteria, price (0.261), availability (0.206), quality (0.200), position (0.106), quantity (0.102), MOQ (0.060), delivery (0.038), payment method (0.027). The results of the TOPSIS method obtained the value and sequence of suppliers, AB (0,587 - 21,0%); AC (0,764 - 27,3%); AD (0,565 - 20,2%); AE (0,490 - 17,5%); AF (0,397 - 14,1%).